THE TRADITIONAL CULINARY TOURISM PROGRAM IN BOGOR CITY, WEST JAVA BASED ON TOURIST PREFERENCES - Rahayu, Kania Sofiantina; Dyah Prabandari; Annisa Rizkiriani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Bogor is a city that represents a blend of traditional Sundanese culture, colonial culture, and the modernity of a metropolitan city. A variety of dishes are offered, ranging from traditional regional specialties to modern fast food. Bogor City is worthy of being a Culinary Destination Area because culinary tourism in Bogor City offers various types of modern and traditional food. Culinary tourism in Bogor City is dominated by modern culinary tourism. This condition is one of the factors that make traditional food rarely found. The culinary distribution of Bogor City is dominant in the city center and the distance between culinary tourism locations is close together, making it easier for tourists to find various culinary delights. This condition has the potential to plan a culinary tourism program. This study aims to identify the motivations, perceptions, and preferences of tourists and Bogor traditional food producers/traders regarding planning traditional culinary tourism programs, identify the readiness of producers/traders in planning traditional culinary tourism programs, and plan Bogor City traditional culinary tourism programs. The output of this research is tourism programs and promotional media. The research respondents were as many as this research. The data were analyzed using the Principal Component Analysis statistical test. Based on the results of the analysis, the indicators with the highest Reflective Interrelation Value are indoor events (0.866), Daily Tour programs (0.844), and Deposit financing.